Some utilisation options for cattle dung as soil amendment and their effects in coarse-textured Ultisols and maize growth - Solange Ndzeshala; Sunday Obalum; Charles Igwe (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Scarcity of effective manures frustrates the adoption of organic-based soil fertility management in tropical agriculture. Cattle dung (CD) is hugely generated but underutilised due to its high carbon-nitrogen ratio and low mineralisation rate compared with poultry droppings (PD), hence the need to enhance CD's efficacy.Method Effects of CD utilisation options on fertility of sandy-loam Ultisols and maize growth were assessed under glasshouse conditions. Four options, CD in its cured form (CD), CD-derived biochar (BC), CD water-soaked CD fermentate (FM) and CD+urea (CDU), were assessed against cured PD and NPK-15:15:15 as reference manure and fertilizer, respectively, using 5-kg potted soils watered to and maintained at field capacity. Organic amendments were added at 10-t-ha–1 equivalents before sowing except FM added alongside CDU’s urea at 250 kg ha–1 equivalent after sowing. Also, NPK-15:15:15 was added at 400 kg ha–1 equivalent after sowing.Results After 9 weeks, BC, CDU and PD had similar effects on soil pH, organic matter, total N and available P which increased by 49-51%, 30-34%, 200-333% and 164-176%, respectively relative to the control. The BC always showed maize plants similar to the tallest ones in PD. Maize dry matter was the highest in CDU/PD (35.06-35.56 g pot–1) and the lowest in control (9.56 g pot–1). Residual effects showed that BC and PD maintained the increases in soil pH, while CDU/PD always showed tallest plants and enhanced dry matter over the rest except BC. Soil pH, Mg2+ and base saturation together caused 93% of treatments’ effects on dry matter.Conclusion Converting CD to BC or supplementing it with urea (CDU) in coarse-textured tropical soils could have prolonged liming and/or biomass productivity-enhancing effects as PD.